Interaction of Growth Pole and Shannons Entropy in Banda Aceh City - Fadhly, Noer; Rusdi, Muhammad; Bulba, Alfa Taras (Graduate School of Universitas Syiah Kuala, 2024)
The development of growth poles, urban activity centers, and service centers in Banda Aceh City has impacted the spread, a complex urban phenomenon challenging to measure due to urban sprawl. The increasing need for space in urban areas drives the development of suburban and random areas (urban sprawl). This is evident from the BPS Banda Aceh City data for 2024, where the population increased by 25.61% post-tsunami, affecting the density of each sub-district in Banda Aceh City. Research using Shannons Entropy Method and the Gravitational Model is necessary to prevent uneven growth in the city of Banda Aceh. The application of Shannons Entropy method in Banda Aceh City from 2010 to 2020 can be seen in the Relative Entropy Matrix, which shows that the linear spread pattern (Quadrant C) is more dominant in the districts of Banda Raya, Baiturrahman, Kuta Raja, Kuta Alam, Lueng Bata, and Syiah Kuala. The urban spread pattern of Banda Aceh tends to move towards the East, largely due to the landform factors that are very suitable for being developed into built-up areas. Meanwhile, the results of the gravity analysis show that the area of interaction with the most substantial interaction value as the growth pole is the interaction between Kuta Alam District and Baiturrahman District, with a value of 190,617,812.346 interactions. The results of identifying the factors influencing the development of urban sprawl, such as the distance to the CBD, the GRDP of Banda Aceh City, changes in land use, housing demand, and the availability of infrastructure facilities in the districts of Banda Aceh City, can be concluded that there is an influence of urban sprawl on the spatial structure and regional patterns in Banda Aceh City.